1, 1′‐Bis(pyrazol‐4‐yl)ferrocenes: Potential Clip Ligands and Their Supramolecular Structures. Issue 2 (2nd November 2016) - Veronelli, Mattia; Dechert, Sebastian; Schober, Anne; Demeshko, Serhiy; Meyer, Franc
Abstract : Two ferrocene derivatives with pyrazoles appended at their C‐4 position to both cyclopentadienyl (Cp) rings have been synthesized, namely, 1, 1′‐bis(1 H ‐pyrazol‐4‐yl)ferrocene (H2 H L) and 1, 1′‐bis(3, 5‐dimethyl‐1 H ‐pyrazol‐4‐yl)ferrocene (H2 Me L). In the solid state, these are shown crystallographically to form supramolecular aggregates through intermolecular NH··· N hydrogen bonds in either a dimeric (H2 H L) or trimeric (H2 Me L) arrangement. Variable‐temperature NMR spectroscopy and diffusion‐ordered spectroscopy (DOSY) evidenced the presence of [H2 Me L]3 trimers in [D8 ]toluene solution, whereas both H2 H L and H2 Me L exist as monomers in deuterated N, N ‐dimethylformamide ([D7 ]DMF) even at low temperatures. The kinetic parameters for the NH tautomerism have been determined. In their dianionic forms, both of these hybrid ferrocene/pyrazole molecules serve as ligands towards Cu I, Ag I, and Au I ions. Matrix‐assisted laser desorption/ionization mass spectrometry (MALDI MS) revealed the formation of [M2 R L]3 hexametallic complexes, the structures of which are suggested to have D 3 h symmetry with two metallomacrocyclic [M(µ‐pz)]3 (pz = pyrazolate) decks connected by three ferrocene clips. Mössbauer spectra and preliminary luminescence data were collected for the proligands and the resulting complexes. Owing to the insolubility of the coinage‐metal complexes, the electrochemical properties could be measured only for the two H2 R L proligands. Abstract : Supramolecular double deckers of the common pyrazolate‐based [M(µ‐pz)]3 metallomacrocycles (M = Cu I, Ag I, Au I ; pz = pyrazolate) are assembled from ferrocene derivatives with two C‐4‐appended pyrazole rings. The ferrocene/pyrazole proligands H2 R L form dimeric or trimeric supramolecular aggregates through intermolecular NH··· N hydrogen bonds, both in the solid state and in solution.